Discharge Mode Analysis in a Dielectric Barrier Discharge Reactor with Two Bar‐Shaped Electrodes Separated by a Central Slit. Issue 12 (5th November 2013) - Hur, Min; Kang, Woo Seok; Song, Young Hoon; Kim, Dong Joo; Yu, Sang Seok
<x xml:space="preserve">Abstract</x> The discharge mode of a dielectric barrier discharge reactor with two bar‐shaped electrodes separated by a central slit is analyzed. The spatial and temporal distributions of seed electrons and surface charges in a current pulse significantly influence the start position and propagation of the discharge in the subsequent pulse. The discharge structure during the negative current pulse is separated into a cathode glow, a positive column, and an anode glow, whereas only a cathode glow is observed during the positive current pulse. A filamentary mode, which is caused by localizations of the space charge field, occurs only during the positive current pulse. The filamentary nature in the positive current pulse is strengthened with increases in the gap distance and applied voltage.<inline-graphic xlink:href="ark:/27927/pgg3zs55s9p" content-type="ppap201300046-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />